Bluetooth Hyperosmia: Chemosensory Variant of Delusional Somatic Symptom Disorder - S. Kalita; D. Birwatkar; A. Hirsch (European Psychiatry, 2023)
Introduction Subjective hyperosmia, as a manifestation of belief of exposure to Bluetooth transmission, with testing demonstrating the absence of true hyperosmia, has not heretofore been described. Objectives Correlation of Bluetooth transmission with subjective hyperosmia. Methods